2022
DOI: 10.1101/2022.02.22.481498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recombination smooths the time-signal disrupted by latency in within-host HIV phylogenies

Abstract: Within-host HIV evolution involves latency and re-activation of integrated provirus that has the potential to disrupt the temporal signal induced by the evolutionary race between host immune responses and viral evolution. Yet, within-host HIV phylogenies tend to show clear, ladder-like trees structured by the time of sampling. Recombination complicates this dynamic by allowing latent HIV viruses to re-integrate as fragments in the genomes of contemporary virus populations. That is, recombination violates the f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…When analyzing the real HIV-1 anatomical tissue sequence data, for consistency, we used bionj [36] in the R [37] package ape [38] under a TN93 substitution model, with 1000 bootstrap replicates. While neighbor-joining trees have been shown to be inferior to maximum likelihood trees in HIV research [39], we recently showed that in terms of both topological and branch length summary statistics, they give comparable results when recombination is operating [33].…”
Section: Phylogenetic Inferencementioning
confidence: 88%
See 3 more Smart Citations
“…When analyzing the real HIV-1 anatomical tissue sequence data, for consistency, we used bionj [36] in the R [37] package ape [38] under a TN93 substitution model, with 1000 bootstrap replicates. While neighbor-joining trees have been shown to be inferior to maximum likelihood trees in HIV research [39], we recently showed that in terms of both topological and branch length summary statistics, they give comparable results when recombination is operating [33].…”
Section: Phylogenetic Inferencementioning
confidence: 88%
“…While the ARG displays the correct evolutionary history, it is difficult to view, and is still very difficult if not impossible to infer on larger real data [43][44][45][46]. On the other hand, standard bifurcating phylogenies cannot properly display recombination, but they are, nevertheless, affected by recombination [33,47]. Therefore, we used a recently developed method to resolve the ARG into an expected standard bifurcating tree to compare our modelling to the familiar phylogeny [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, low viral loads in individuals on incompletely suppressive ART may lead to correspondingly low recombination rates, mitigating recombination of distinct drug resistance mutations on different genetic backgrounds as a path to multi-drug resistance (speculated in [13]). Lower rates of recombination in lower viral load populations may also make phylogenetic approaches that rely on treelike evolutionary divergence more tractable to apply without requiring ancestral recombination graphs [8]. While we did not have access to samples with extremely low viral loads near the limit of detection, future investigations could determine if previously reported average recombination rates ( ≈ 1.4 × 10 − 5 ) can explain low viral load patterns of linkage decay.…”
Section: Discussionmentioning
confidence: 99%